Dinamika Peran Gender dalam Keluarga Modern: Studi pada Pasangan yang Memilih Peran Ayah sebagai Pengasuh Utama - Fritz Hotman Syahmahita Damanik (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The evolution of gender roles in modern families has become increasingly dynamic, including the phenomenon of fathers serving as primary caregivers. This study explores the factors driving this role shift, the challenges faced by fathers as primary caregivers, and societal responses to this change. Based on interviews with several fathers who have taken on the primary caregiving role, the study finds that economic factors, job flexibility, and changing perceptions of gender equality contribute to this decision. However, these fathers encounter challenges such as adapting to childcare responsibilities, social pressures, and time management. Societal views on this phenomenon vary, ranging from initial skepticism to gradual acceptance. This study highlights that gender roles in modern families are becoming more flexible and can be adjusted according to each family's needs and circumstances. With a broader understanding of gender role flexibility, society can better support fathers who take on the role of primary caregivers. The findings of this research are expected to provide valuable insights for families, academics, and policymakers in promoting gender equality within households.